Komparasi Pernikahan Bangsawan Suku Sasak dan Bangsawan Hindu di Kecamatan Batulayar, Kabupaten Lombok Barat, Nusa Tenggara Barat - Lalu Aji Sanjaya Putra; Jamaluddin .; Kamaruddin Zaelani (Universitas Muhammadiyah Makassar, 2024)
Marriage in various cultures in Indonesia serves as a bond between families and a medium for passing on traditions, norms, and socio-cultural identity. This study aims to examine the comparative marriage practices of Sasak aristocrats and Hindu aristocrats in Batulayar Sub-district, West Lombok Regency. It focuses on the similarities, differences, and changes resulting from modernisation. Using a qualitative approach and a comparative study design, this research analyzes the traditional marriage practices of both groups and the impact of modernisation on their rituals. Data were collected through in-depth interviews and direct observation, with thematic analysis employed for interpretation. The findings reveal that Sasak noble weddings place greater emphasis on local traditions and Islamic beliefs, aiming to strengthen extended family and community ties. In contrast, Hindu noble marriages are rich with spiritual symbolism, where the primary goal is the attainment of moksha. Both wedding traditions highlight family values and community involvement, with parental blessings and negotiations being integral to the ceremony. However, differences arise in ritual execution, with Hindu aristocratic marriages involving more extensive and complex religious ceremonies. Modernisation has significantly influenced marriage practices in both groups. Some families have begun to incorporate modern elements into their wedding ceremonies, while many continue to strive to preserve their cultural identity. This research also underscores the importance of education and intercultural dialogue in maintaining diversity and fostering social cohesion.:Marriage, nobility, Sasak ethnic, Hindu nobility, ritual, culture, pluralism.